Peran Indonesia dalam Implementasi Hukum Internasional untuk Melindungi Kepentingan Nasional di Wilayah Pesisir: Analisis terhadap Pengaruh dan Kontribusi UNCLOS - Fathullah, Abdusyahid Naufal; Rahmi, Dinda Fuaina; Ghonia, Ninna (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesia, as the largest archipelagic country in the world, has a very large strategic interest in its coastal areas. The sea is not only an abundant natural resource, but also a vital route for trade and communication. In this context, the implementation of international law, especially the United Nations Convention on the Law of the Sea (UNCLOS), is very crucial to protect Indonesia's national interests. Through normative research and case studies, this research examines national laws and regulations, maritime policies, and relevant practices. The results of the study show that Indonesia has taken significant steps in implementing UNCLOS, such as the establishment of an Exclusive Economic Zone (EEZ) and the continental shelf. However, there are still a number of challenges in harmonizing international and domestic law, as well as in the face of the complexity of contemporary maritime issues. The case study of the North Natuna Sea dispute underscores the importance for Indonesia to continue to strengthen its legal position in order to defend its rights in the maritime area.